(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2019)
In this article the author considers the trauma of memory in the artistic discourse of postmodern dramaturgy. The attention is drawn to revealing symbolic and psychological aspects of the reception of “official history”: overlaying and interpenetration of archaic and social myths, initiation models; interrelation of the concept “Ourselves/Strangers”; peculiarities of mind and memory of the past; artistic embodiment of the archetype images of the Motherland/Home; interpretation of the nation’s mental code.